Tomoelastography of the abdomen: Tissue mechanical properties of the liver, spleen, kidney, and pancreas from single MR elastography scans at different hydration states - Dittmann, Florian; Tzschätzsch, Heiko; Hirsch, Sebastian; Barnhill, Eric; Braun, Jürgen; Sack, Ingolf; Guo, Jing (Magnetic resonance in medicine, 2017)
Purpose To develop a compact magnetic resonance elastography (MRE) protocol for abdomen and to investigate the effect of water uptake on tissue stiffness in the liver, spleen, kidney, and pancreas. Methods Nine asymptomatic volunteers were investigated by MRE before and after 1 liter water uptake. Shear‐wave excitation at four frequencies was transferred to the abdomen from anterior and posterior directions using pressurized air drivers. Tomographic representations of shear‐wave speed were produced by analysis of multifrequency wave numbers in axial and coronal images acquired within four breath‐holds or under free breathing, respectively. Results Pre and post water, stiffness of the spleen (pre/post: 2.20 ± 0.10/2.06 ± 0.18 m/s) and kidney (pre/post: 1.93 ± 0.22/1.97 ± 0.23 m/s) was higher than in the liver (pre/post: 1.36 ± 0.10/1.38 ± 0.13 m/s) and pancreas (pre/post: 1.20 ± 0.12/1.20 ± 0.08 m/s), all P < 0.01. Accounting for four drive frequencies, water drinking only changed the splenic stiffness (–6%, P = 0.03), whereas in the frequency range from 50 to 60 Hz the effect became significant also in the pancreas (–6%, P = 0.04) and liver (+3%, P = 0.03). Elastograms of the kidney in coronal view clearly depicted higher stiffness in cortex than in medulla. Conclusion Tomoelastography reveals sensitivity of tissue mechanical properties to the hydration state of multiple abdominal organs within one scan and in unprecedented resolution of anatomical details. Magn Reson Med 78:976–983, 2017. © 2016 International Society for Magnetic Resonance in Medicine.